A hódmezővásárhelyi Turul Szövetség működése : 1925-1944 - Zeman, Ferenc (Közép-Európai Közlemények, 2016)
The Turul was the biggest Hungarian student association during the interwar period. Most of its members – in the 1920s and 1930s – followed the protection of race ideology and studied in the higher education. On 10 October 1925 the college and university students of Hódmezővásárhely founded the local chapter of the Turul Association, which was named Count Miklós Bercsényi Fraternal Mixed Group. In 1932 the name of the organization was changed for Count Miklós Bercsényi Fraternal Association. The most significant event of the association was the line-up of the Countryflag in Hódmezővásárhely, which was consecrated in the Whitsun of 1934. The local association – next to its activity in the public life – handled social, cultural and political questions. In their teach-in they entertained well-known politicians and writers. From the final chapter of our study the reader can be informed about the position of the Bercsényi in the national Turul Association.